GAP ANALYSIS OF TRAVELOKA.COM: HOTEL CONSUMERS’ EXPECTATIONS AND PERCEPTIONS OF THE WEBSITE - Fransisca Andreani; Gabriella Winata; Eunike Halim (Jurnal Manajemen dan Kewirausahaan, 2018)
Traveloka.com is one of the famous online travel agents to make hotel reservation in Indonesia. Consumers making online hotel reservation can sometimes find that the performance of the website does not meet their needs. This study is to analyze the gap between hotel consumer expectations and perceptions on the website dimensions of traveloka.com. It is a quantitative method with 150 respondents who made hotel reservations through traveloka.com. The analysis techniques used are mean test and paired t-test. The results show that there are significant gaps between consumer expectations and perceptions on the website dimensions of traveloka.com. The biggest gap is on the images displayed which are in accordance with the real conditions.